Tajikistan - Quality of Child Health Services - World Bank (World Bank, 2012)
The Government of Tajikistan has identified Primary Heath Care (PHC), and Maternal and Child Health (MCH) as top priorities in its first Comprehensive National Health Sector Strategy (2010-2020). The study findings which closely mirror those of the 2009 World Health Organization (WHO)/United Nation children's Fund (UNICEF) Integrated Management of Childhood Illness (IMCI) survey will be of great concern to the Ministry of Health and should provide the impetus to take immediate remedial actions. Much remains to be done to improve the overall quality of primary health care services for under-five children. Two main issues are highlighted by this study. Firstly, the quality of primary health care services provided to children is lacking in many areas, irrespective of the PHC provider's type of training. Second, is that the family medicine and IMCI training programs and methods require further enhancement to ensure that the service quality for children improves. The study also finds that supervision of PHC workers is irregular, and training does not seem to be performed systematically to improve children's health outcomes.